Dependence of Bacterial Protein Adhesins on Toll-Like Receptors for Proinflammatory Cytokine Induction - Hajishengallis, George (American Society for Microbiology, 2002)
Toll-like receptors (TLRs) are important signal transducers that mediate inflammatory reactions induced by microbes through pattern recognition of virulence molecules such as lipopolysaccharide (LPS) and lipoproteins. We investigated whether proinflammatory cytokine responses induced by certain bacterial protein adhesins may also depend on TLRs. In differentiated THP-1 mononuclear cells stimulated by LPS-free recombinant fimbrillin (rFimA) from Porphyromonas gingivalis, cytokine release was abrogated by monoclonal antibodies (MAbs) to CD14 and TLR4 but not to TLR2. Similar experiments using anti-β2 integrin MAbs suggested that β2 integrins (CD11/CD18) also play a role in cytokine induction by rFimA or native fimbriae. Minor fimbriae (distinct from the fimA-encoded major fimbriae) of P. gingivalis induced proinflammatory cytokine release in a CD14- and TLR2-dependent mode. Cytokine induction by BspA, a leucine-rich repeat protein from Bacteroides forsythus, depended heavily on CD14 and TLR2. We also found that the ability of the streptococcal protein AgI/II to stimulate cytokine release depended partially on CD14 and TLR4, and the AgI/II segment that possibly interacts with these receptors was identified as its N-terminal saliva-binding region. When THP-1 cells were exposed to rFimA for 24 h, surface expression of CD14 and CD18 was decreased and the cells became hyporesponsive to cytokine induction by a second challenge with rFimA. However, tolerance induction was abolished when the THP-1 cells were pretreated with rFimA in the presence of either anti-CD14 MAb or anti-TLR4 MAb. Induction of cross-tolerance between rFimA and LPS correlated with downregulation of the pattern recognition receptors involved. Our data suggest that the CD14-TLR2/4 system is involved in cytokine production and tolerance induction upon interaction with certain proinflammatory bacterial protein adhesins.